Modification of plasma-sprayed TiO2 coatings characteristics via controlling the in-flight temperature and velocity of the powder particles - Cizek, Jan (2014)
The study presents a comprehensive research on the plasma spray fabrication of TiO2 coatings with microstructural properties adjustable via controlling the respective in-flight properties of the feedstock particles. The in-flight properties can be, in return, governed by tuning the plasma system spray parameters. By determining and linking the two interrelationships, a connection between the important coating characteristics (composition, microstructure, surface and mechanical properties) to the plasma system settings was established. It was shown that by changing the values of six parameters representing the flexibility of the plasma system, the temperatures and velocities of the particles within the jet can be altered from 2125 to 2830 K and 137 to 201 m s−1, respectively. The values of the in-flight temperature critically influenced the efficiency of the coating build-up (values ranging from 8 to 84 μm per 1 torch pass) and the content of anatase phase in the fabricated coatings (0-5.8%), while the in-flight velocity of the TiO2 particles was found to be connected to the porosity of the coatings (ranging from 14.4 to 26.2%) and the adhesion strength at the coating-substrate interface (2.6 × difference).